COST MANAGEMENT IN AN ACADEMIC HEALTH CARE PRACTICE - Quintana, Olga; Ortiz, Cesar (Anais do Congresso Brasileiro de Custos - ABC)
Increasing competition for the health care dollar has made cost containment one of the most significant issues facing health care managers. This is particularly relevant in the United States where health care practices have been driven by Federal and local governments to control health care costs. This paper discusses an accounting system developed for a health care practice which facilitates management decisions by allowing a detailed review of revenues and expenses for each center, division and the entire entity. Cost accounting techniques are applied to examine each academic center in order to classify each center into a profit center or a deficit producing center. Profit center's revenues exceed direct and indirect "overhead" expenses. The resulting contribution or gain is used to finance deficits from other centers. Functionally, a profit center will receive a share of the gains from the program centers and a bonus. Physicians with well established practices generally fall into this category. Deficit producing centers are those in which direct and indirect expenses exceed revenues. New practicing physicians usually generate a deficit. There are also centers that will probably never break even, however the type of services provided by these centers is deemed to be essential and cannot be discontinued without compromising the quality of the health care delivery system. These centers are also classified as deficit centers.